2022
DOI: 10.3390/cancers14174230
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Transoral Robotic Thyroidectomy for Thyroid Tumor: A Systematic Review and Meta-Analysis

Abstract: Background: To assess the safety and effectiveness of transoral robotic thyroidectomy (TORT) in thyroid tumor. Methods: PubMed, Embase, Web of Science, SCOPUS, Cochrane database, and Google Scholar up to June 2022. Studies comparing outcomes and complications between TORT and control groups (robotic bilateral axillo-breast, trans-axillary, postauricular approach, conventional open thyroidectomy (OT), and transoral endoscopic approach) were analyzed. Results: Ten studies of 1420 individuals. The operative time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
2
4
0
Order By: Relevance
“…In addition, TOETVA is becoming popular worldwide because of its excellent cosmetic effects. In consensus with our previous study (10, 16), many recent studies have reported that TOETVA is comparable in safety and efficacy to conventional open surgery (3,4,17). Therefore, the implementation of ambulatory TOETVA is feasible.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, TOETVA is becoming popular worldwide because of its excellent cosmetic effects. In consensus with our previous study (10, 16), many recent studies have reported that TOETVA is comparable in safety and efficacy to conventional open surgery (3,4,17). Therefore, the implementation of ambulatory TOETVA is feasible.…”
Section: Discussionsupporting
confidence: 84%
“…The absence of any cases of permanent hypoparathyroidism or recurrent laryngeal nerve injury within our study population not only corroborates the high safety standards of the procedure but also serves as a testament to the reliability of robotic assistance when wielded by well-trained surgical hands ( 16 ). This evidence reinforces the notion that robotic thyroidectomy, when performed by skilled surgeons, is not only innovative but also a reliably safe intervention, setting a new benchmark for patient teatment in thyroid surgery ( 17 ).…”
Section: Discussionsupporting
confidence: 81%
“…The safety of the procedure was the motor theme from the topic map analysis ( Figure 4B ), and it is believed that this topic will continue to be a hot topic of research in the future. Transoral robotic thyroidectomy has become popular with a wide range of surgeons over the last three years, and its safety, quality of life and effectiveness have aroused much scholarly attention ( 28 , 44 ).…”
Section: Discussionmentioning
confidence: 99%